Precautionary Saving and Old-Age Pensions - Knut A. Magnussen (Statistics Norway, Research Department, 1994)
A precautionary saving model is extended to include old-age pensions and provides the framework for an empirical analysis of the relation between old-age pensions and private consumption. Norwegian macro-data for socioeconomic groups of households are used to estimate consumption functions for workers and pensioners. We find no effects from various approximations of expected pension-income to consumption for workers, but results indicate some influence from labour-income uncertainty. Income elasticities are found to differ considerably between the two groups of households. Implications for effects on aggregate saving from pension policies and of ageing populations are discussed.
Keywords: D91; E21; H55; 330